OPTIMIZATION OF THE CUTTING EDGE GEOMETRICAL PARAMETERS BASED ON FINITE ELEMENT SIMULATION OF TURNING INCONEL 718 - CHENG Xin; LIU QingFeng; WANG NingChang; JIANG Feng (Jixie qiangdu)
A two-dimensional finite element model of orthogonal cutting Inconel 718 has been built by Third Wave Advant Edge to obtain the distribution of temperature and stress under different parameters of the cutting edge. The cutting force predicted by the finite element method（ FEM） showed good agreement with the experimental results. The optimize processes of the cutting edge parameters has been proposed and the effect of cutting edge parameters on cutting stress and cutting temperature have been analyzed. Then,the optimal parameters of cutting edge on the processing of nickel-based alloy are selected. It finds that,with given relief angle of 7°,the optimal rake angle is 6°and the optimal cutting edge radius is 60μm. Basically,with the increase of the rake angle,cutting temperature gradually increases and the tool stress decreases firstly and then increases,and the temperature of chips decreases and the high stress area expands to the flank face of tools. With the increase of the cutting edge radius,cutting temperature increases and tool stress decreases firstly and then increases,and stress concentration of cutting edge is weakened.